UNIVERSITY, LINK TO SOCIETY AND IMPROVEMENT PROCESS - Chávez Cruz, Gonzalo Junior (2016)
This article analyzes the Organic Law on Higher Education of Ecuador with regards to the links and the aspects that force the Higher Education Institutions to act on the expectations and needs of the community, considering the national planning, the development regime, the worldwide scientific, humanistic and technological improvement, and the cultural diversity in the country. The importance of the relation with the community is described and it is highlighted as the strongest indicator of universities categorization at the present time. For that effect, some ideas are provided on how a comprehensive working model should be structured for effective linkage among the university, business and community, using as reference the Academic Unit of Business Science.